صوت الشعر: صدي الطين قراءة سيميائية في ديوان "صوت برائحة الطين" لسعود بن سليمان اليوسف - أبو طالب، إبراهيم محمد (نادى الرياض الأدبى, 2018)
هذه مقاربة في ديوان الشاعر الدكتور سعود بن سليمان اليوسف الذي يعد واحدا من الأصوات الشعرية السعودية الشابة والناضجة بما يحمله من رؤية إبداعية تقوم على قراءة واعية للموروث الإبداعي العربي الشعري واستثمار للصوت التاريخي والسردي، وينعكس ذلك في توظيفه في عالمه الشعري الخاص ذي الصوت الواضح من خلال استثمار القناع، وتقنيات استدعاء الشخصيات الإبداعية والتراثية وغيرها، مستثمرا ذلك في مداخل النص وعتباته التي تتداخل في انسجام واضح مع بنية النص الشعري وعالم القصيدة في تركيبها وفنيتها، ويفتح ذلك التوظيف دلالات النص على آفاق القراءة المنتجة؛ لأن النص عميق المعنى، وقد سعت هذه المقاربة إلى بيان ذلك باستعمال آليات المنهج السيميائي الذي يعد الأقدر على استنباط تلك الدلالات ببيان بيان ممكنات النص ابتداء بالعنوان والغلاف الخارجي، والنصوص الموازية المختلفة، وانتهاء ببنية النص الشعري نفسه، وقد بينت المقاربة مدى ذلك الترابط وجمالياته.
This is a study of the collection of poems of the poet Dr. Saud bin Suleiman al-Yusuf who is one of the young and mature Saudi poetic voices with his creative vision which has a conscious reading of heritage of poetic, and an investment of history and narrative. This is reflected in his employment in his own poetic world which has its own special characteristics through the Investment of the mask and the techniques of recalling the creative and heritage characters, and others, employing in the entrances of the text and that overlap in a clear harmony with the structure of the poetic text, and the world of the poem in its composition and aesthetics, and that employment guides the semantics text to the prospects of productive reading because of the deep meaning of the text. This study tried to state that through the semiotic approaches, which classified as the best approach to derive that meanings by employing the text’s contents starting with the title, outer cover, various parallel texts, and ending with the structure of the poetic text itself. Furthermore, the study shows the extent of coherence and aesthetics.
Keywords: الادب العربي -- الشعر الادبي -- اليوسف، سعود بن سليمان